Analisis Persepsi Civitas Akademika terhadap Implementasi Perkuliahan E-Learning Selama Pandemi Covid-19: - Dedi Junaedi; Qowaid Qowaid; Moh Romli; Amie Primarni (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
ABSTRACT The Covid-19 pandemic has forced educational institutions to implement an online learning system. This study aims to explore the cognitive, affective and conative aspects of e-learning implementation; and analyzing the influence of age, gender differences, status and area on the implementation of e-learning at the IAI-N Laa Roiba campus. The research method used is a combination of descriptive analysis and quantitative analysis with a dummy variable regression approach. Research respondents were the academic community of IAI-N Laa Roiba. The results are as follows: e-learning is generally carried out using the Google Classrom application, Google Meet and Zoom Meeting. Other models are WA and website portals. The cognitive aspects of the implementation of e-learning during a pandemic are influenced by effective, conative aspects, and to some extent are influenced by factors of age, gender, education and location of domicile. The affective aspect is obeyed by the cognitive and conative aspects, and to some extent it is influenced by the level of education and gender. While the conative aspect is influenced by cognitive and affective aspects, and to some extent is influenced by the level of education. The factors of age, gender, status, and location did not significantly influence the conative aspects of e-learning implementation during the Covid-19 pandemic. Keywords: affective, e-learning, cognitive, conative, Covid-19 pandemic